The Therapeutic use of Radon: A Biomedical Treatment in Europe; An "Alternative" Remedy in the United States - Barbra E. Erickson PhD (SAGE Publishing, 2007)
There is a growing recognition in the United States and Europe that health care is driven to a significant extent by an emphasis on consumer choice and demand. As consumers, people regularly choose their own solutions for health promotion and maintenance, solutions which may or may not be sanctioned by mainstream medicine. Radioactive radon therapy exemplifies a non-sanctioned treatment eagerly sought by certain patients, but scorned or dismissed by many physicians. This is certainly the case in the United States, where well-publicized Environmental Protection Agency (EPA) warnings portray radon as a potential carcinogen. Between 1997 and 2001, I worked with a population of arthritis sufferers who expose themselves to radon gas in Montana radon health mines in order to alleviate their symptoms. In this paper I discuss the decision-making process involved in using radon, and compare the Montana radon health mine facilities with selected radon mines and spas in Europe.